Developing Psychological Contracts of Justice in Improving Employee's Satisfaction at Perum Damri - Akmal, Akmal; Azliyanti, Elfitra (Management Institute Faculty of Economics Universitas Andalas, 2019)
This study aims to examine the predictors and consequences of a fair psychology contract. There are relationships between the degree of reciprocal trust and fair psychological contracts, reward mechanisms for fair psychology contracts, assessment of actual performance to a psychological contract of justice, intrinsic motivation to equitable psychology contracts, equitable psychological contracts on job satisfaction and Intrinsic motivation and Job satisfaction. The population of this study is 205 staff at Perum Damri Regional Division II and data was collected using a purposive sampling technique. The criteria of the respondents chosen were staff or employees who had worked in Damri's general company for at least 1 year. Data analysis techniques in research using software smart PLS 2.0 M3. This study contains 6 hypotheses and from the research, the results of reciprocal degrees of trust influence the fair psychology contract, but the progressive reward mechanism, the assessment of actual performance and intrinsic motivation have no effect. While fair psychology contracts and intrinsic motivation affect employee job satisfaction.